Ementas Escolares Sustentáveis: proposta de critérios para avaliação qualitativa - Adriana Manuela Carvalho de Sousa (2021)
School-age canteens serve an age group that requires differential attention, since the growth and development of their users are largely determined by the meals available there. Thus, the food offer must provide options that promote healthy, safe and sustainable eating. In this perspective, the objective of this work is to contribute to the establishment of criteria that allow the elaboration and evaluation of menus based on the sustainability factor, as well as updating and complementing with criteria expressed in Circular n.º3097/DGE/2018. More specifically, it is intended to add new criteria to the qualitative evaluation tool of menus presented in the "Sistema de Planeamento e Avaliação de Refeições Escolares", in order to be taken into account when preparing a school menu. This is an observational study, with a descriptive and cross-sectional dimension, particularly in the detailed analysis of scientific information on sustainability and in the collection of these and other criteria to be included in the tool. The construction of the final methodology comes from an exhaustive literature review, as well as a consultation of a broad panel of experts qualified in the subject, with different skills in decision-making, specifically academics, managers of companies providing school meals, heads of local authorities and organs members. In order to test the government functionality of the proposed tool, three menu plans were introduced in the final tool. After several adjustments to the initial checklist, namely the introduction of several criteria and the exclusion of others, and also the introduction of a new group, a final checklist with 88 criteria was obtained, grouped by 7 groups, and duly weighted, depending on the contribution that each one reveals. The creation of the aforementioned tool shows its relevance, as it encompasses the aspects of health and sustainability at the same time, facilitating the preparation, monitoring and evaluation of school menus by the responsible professionals, with a view to improving the offer.